Beetles (Coleoptera) of Peru: A Survey of the Families. Monotomidae Laporte, 1840 - McElrath, Thomas (2017)
The diversity of the beetle family Monotomidae is summarized for the country of Peru. One subfamily, three tribes, three genera, and four species are recorded. This paper presents the first record of this family in Peru, as part of the 'Beetles of Peru' project. Diagnostic characters for the family are given. This is only a preliminary checklist; Many specimens were not identifiable past genus with current literature. The diversity of Monotomidae will expand considerably with additional surveys and sampling work within the country.